Efficacy and safety of yoga for the management of chronic low back pain: an overview of systematic reviews - Zhang, Xianshuai; Chang, Tianying; Hu, Wenlong; Shi, Mingpeng; Chai, Yating; Wang, Siyi; Zhou, Guohui; Han, Mingze; Zhuang, Minghui; Yu, Jie; Yin, He; Zhu, Liguo; et al. (Frontiers in Neurology, 2023)
Background: Yoga is a non-pharmacological conservative therapeutic modality, which can be employed for the management of chronic low back pain (CLBP). In this overview, we have summarized and evaluated data from current systematic reviews (SRs) on the use of yoga for CLBP. Methods: We comprehensively searched SRs on the use of yoga for CLBP in nine electronic databases from inception to September 2023. The methodological quality was evaluated using the Assessment of Multiple Systematic Review Scale-2 (AMSTAR-2). The reporting quality of the included SRs was evaluated using the Preferred Reporting Item for Systematic Review and Meta-Analysis-2020 (PRISMA-2020), and the quality of data was graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Two independent researchers performed the screening, data extraction, and quality assessment process of SRs. Results: A total of 13 SRs were included. The results of the AMSTAR-2 indicated that the methodological quality of the included studies was relatively low. The PRISMA-2020 checklist evaluation results indicated that methodological limitations in reporting, especially regarding data processing and presentation, were the main weaknesses. The GRADE assessment indicated that 30 outcomes were rated moderate, 42 were rated low level, and 20 were rated very low level. Downgrading factors were mainly due to the limitations of the included studies. Conclusion: Yoga appears to be an effective and safe non-pharmacological therapeutic modality for the Management of CLBP. Currently, it may be exhibited better efficacy in improving pain and functional disability associated with CLBP. However, the methodological quality and quality of evidence for SRs/MAs in the included studies were generally low, these results should be interpreted cautiously.